Characteristics of Simulated Workplace Neutron Standard Fields - Thiem, Le Ngoc; Quynh, Nguyen Ngoc; Linh, Dang Thi My; Huong, Phan Thi (Communications in Physics, 2020)
This paper presents the development of simulated workplace neutron standard fields at the Institute for Nuclear Science and Technology with the 241Am-Be source moderated by polyethylene spheres with diameters of 15 cm and 30 cm. The characterization of the standard fields (in terms of neutron fluence rates and neutron ambient dose equivalent rates) was performed using Bonner sphere spectrometer system together with MAXED and FRUIT unfolding codes. The related quantities such as neutron dose equivalent-averaged energies and fluence-to-ambient dose equivalent conversion coefficients were also determined. The discrepancies of values are satisfied the standard uncertainty criteria as recommended by the International Standard Organization 12789 series. It implies that the simulated workplace neutron standard fields can be applied in the practical works for calibration purposes